1633e Is paper dust in soft tissue mills a problem?. (24th April 2018) - Andersson, E
Abstract : More dust is generated in the production of soft tissue paper than in production of other paper products. In earlier days 10 and even up to 30 mg/m 3 total dust was not unusual in this industry. We updated an earlier cohort of soft tissue mill workers and included more mills 2006. Inclusion criteria was >1 years work 1960–2006, 8353 were included, 40% females. We did more dust measurements and obtained mill measurements and information on production changes. A mill-specific job exposure matrix for paper dust was developed on department level and sometimes also job-specific. That allowed us to assess every mill year for each subject with an estimated mean level of total dust (mg/m 3 ) into one of seven exposure categories. Our main exposure metric in this presentation is worked years with exposure to >5 mg/m 3 total dust. Those working from 1970 and alive 2007 got a questionnaire which 56% answered. As earlier studies on paper dust exposure and lung function have been inconclusive we made spirometry tests in one of the mills (n=198). Every year exposed to >5 mg/m 3 total dust gave 0, 9% loss in predicted FEV1% and 0.6% loss in predicted FVC, a significantly decrease adjusted for pack-years, gender, atopy and body mass index compared to workers never exposed one year or more to >5 mg/m 3 total dust. Cohort mortality 1960–2013 has now been analysed compared to the general population in Sweden. Mortality in asthma and chronic obstructive pulmonary disease was increased in workers with ≥5 years exposure to >5 mg/m 3 total dust both among males and females.